Histoire des textiles en Babylonie, 626-484 av. J.-C. : Production, circulations et usages - Quillien, Louise (Culture and History of the Ancient Near East, 2022)
Textiles were one of the most celebrated products of Near-Eastern craft in Antiquity. In Histoire des Textiles en Babylonie, 626-484 av. J.-C. , Louise Quillien offers an analysis of textile manufacturing, exchanges and uses in Babylonian society. In a context where archaeological textile remains are rare, cuneiform texts provide rich information on this craft. The book demonstrates that through the study of objects, it is possible to highlight a whole section of the economy, culture, religion and social customs of an ancient society, and proposes to immerse the reader in the daily life of the inhabitants of Mesopotamia.